Determinants of Customer Satisfaction in E-commerce: Insights from Shopee Thailand - Homtong, Kunaporn; Sitheechoke, Panuwat (Edelweiss Applied Science and Technology, 2025)
Thailand’s e-commerce sector has grown rapidly, with over 85% of internet users shopping online and Shopee emerging as a top platform. This study aims to examine: (1) the ease of use of the platform that affects customer satisfaction in purchasing products through the Shopee application in Thailand, and (2) the marketing mix (5Ps) that influences customer satisfaction when purchasing products through the Shopee application in Thailand. A quantitative research method was employed, using a sample of 400 consumers with experience purchasing products through the Shopee platform. Data were collected via an online questionnaire and selected through purposive sampling. The research instrument underwent content validity evaluation by three academic experts, and its reliability was tested using Cronbach’s Alpha, yielding a high reliability score above 0.80. Data analysis included descriptive statistics (percentages, means, and standard deviations) and inferential statistics, including correlation analysis and multiple regression analysis, to explore the relationships and influence of independent variables on customer satisfaction. The findings revealed that platform usability and all elements of the marketing mix significantly and positively influence customer satisfaction. In particular, system speed, clarity of product information, fair pricing, effective promotional strategies, and responsive customer service were identified as key factors. These results provide strategic insights for enhancing user experience and aligning digital marketing strategies with Thai consumer behavior in the competitive e-commerce market.